Mesenchymal stromal cells in adipose tissue of breast cancer patients: a cross-sectional study - Gong, Chen; Wang, Jianhua; Cheng, Qun; Ren, Wu; Bai, Jian (Cellular and Molecular Biology, 2020)
Mesenchymal stromal cells (MSCs) are important components of the tumor microenvironment and are believed to facilitate cancer growth affecting cancer cells. We investigated this issue in breast cancer patients. In this cross-sectional study biopsy or mastectomy specimens from breast cancer patients who underwent surgery were evaluated based on the presence of MSCs. Flow cytometric analysis was used to evaluate the expression of CD73, CD90, CD105, and absence of CD11b or CD14, CD79, CD45, and HLA-DR expression as the criteria of MSC presence. Patients were divided into MSC (+) or (-). SPSS software was used to evaluate the association of age, tumor type, tumor size, disease grade, stage, and metastasis with the presence of MSC cells in adipose tissue of specimens. 82 patients with a mean age of 44.43±9.2 years were included in the study. MSC (+) happened in 13 (15.83) patient's samples. A regression model was conducted to evaluate the association of patient characteristics and the MSC positivity. The patient's age was associated with MSC positivity (B=-0.194, p=0.006); and the disease stage was associated with MSC positivity (B=-0.734, p=0.019). Significantly lower age of patients was seen in MSC (+) patients vs. MSC (-) patients (p=0.002). While no difference in the case of tumor type, tumor size, disease grade, stage, and metastasis was seen between two groups (P>0.05). Our result indicated that Mesenchymal stromal cells are seen more in the tumor microenvironment of younger breast cancer patients. Also, patients having mesenchymal stromal cells may have milder disease and lower disease stage.